Kesiapan Pusat Layanan Kesehatan (PLK) B Unair Menghadapi Akreditasi Klinik Pratama - Putri Ayu Anggraeny; Ernawaty Ernawaty (Universitas Airlangga, 2016)
PLK B Unair is one of the first level clinic that owned by Airlangga University in cooperation with Social Security Agency of Health (BPJS). As mandatory by act, PLK B Unair should start to prepare to reach accreditation for first level clinics to realizing quality assurance for health services. This study aimed to know the early achievement of accreditation assessment in accordance with the guidelines Health Ministerial Regulation No. 46/2015. This was descriptive observational study with cross sectional design The documents were traced to identify the completeness according the instrument, and interviewed was did to know some procedures. The results showed that the achievement there is only 51% of all elements assessment in accreditation standards for the readiness of PLK to faced acreditation. Research recomendation leading to the formation of the team for the preparation of accreditation.Keywords: accreditation, first level clinics, quality assurance, accreditation standards